2013
DOI: 10.1063/1.4798254
|View full text |Cite
|
Sign up to set email alerts
|

Semitransparent organic solar cells with hybrid monolayer graphene/metal grid as top electrodes

Abstract: Hybrid transparent monolayer graphene/metal grid is proposed as top electrode of semitransparent organic solar cells. The hybrid electrode using gold grid on flexible polyethylene terephthalate substrate shows very low sheet resistance of 22 ± 3 Ω/□ and high optical transmittance of 81.4%, which is comparable to conventional indium tin oxide/glass electrode. Using lamination process, the layer of poly(3,4-ethylenedioythiophene):poly(styrenesulfonate) doped with D-sorbitol plays an important role in the electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 22 publications
0
40
0
Order By: Relevance
“…252,253 This also open up more routes for searching TEs in optoelectronic devices. Overall, with cheap raw materials and good compatibility with environment-friendly deposition processes, we believe that these attractive materials will be adapted for application as TEs in optoelectronic devices.…”
Section: Resultsmentioning
confidence: 99%
“…252,253 This also open up more routes for searching TEs in optoelectronic devices. Overall, with cheap raw materials and good compatibility with environment-friendly deposition processes, we believe that these attractive materials will be adapted for application as TEs in optoelectronic devices.…”
Section: Resultsmentioning
confidence: 99%
“…Graphene, the ultra-thin 2-D monolayer graphite, is promising due to its outstanding transparency, conductivity, flexibility and chemical stability [20]. Pioneering work has been done by combining CVD-grown graphene with metal grid, resulting in a hybrid TCF with outstanding electrical and optical properties [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…The semitransparent OSC with an inverted structure of graphene/ PEDOT:PSS/PTB7:PC 71 BM/ZnO-NP/PEDOT:PSS/graphene/ glass with graphene as both BTE and TTE, showed a PCE up to 3.35% irradiated from either sides of the device with an AVT of ≈40% and with neutral color. [131] Lin et al [132] reported semitransparent OSCs with the structure of glass/ITO/TiO 2 / P3HT:PCBM/PEDOT:PSS/monolayer graphene/Au grid/PET. The hybrid top electrode with monolayer graphene/Au grid on PET substrate showed low sheet resistance of 22 ± 3 Ω sq −1 and high optical transmittance of 81.4%, which is comparable to ITO/glass electrode.…”
Section: Wwwadvenergymatdementioning
confidence: 99%